Answer:
A(n+1)=A(n)+3, for n>=0 and A(1)=5
Explanation:
This sequence can be expressed in a recursive form. A recursive formula is one where each term can be expressed as a function of its preceding terms. For example; term 5 precedes 8, 8 precedes 11, 11 precedes 14, and 14 precedes 17.
The terms can be expressed as follows;
A(n+1)=A(n)+3, for n>=0 and A(1)=5
where;
A(1): First term
n: nth term
A(n): current term
A(n+1): Next term
d=3: common difference
Since in order to get the next term, one has to add 3 to the preceding term, therefor 3 is the common difference between A(n+1) and A(n)+3
Therefor;
A(n+1)=A(n)+3, for n>=0 and A(1)=5